THE IMPACT OF TECHNOLOGY ON COPYRIGHT: COPYRIGHT DETERMINATION MECHANISM FOR SOUNDS PRODUCED BY ARTIFICIAL INTELLIGENCE - Fitri Wulandari; Lidya Shery Muis (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the legal mechanisms governing copyright ownership of songs produced by artificial intelligence (AI) applications such as Suno, Soundful, and AIVA within the Indonesian legal framework. Method: Employing a normative juridical approach, the research examines relevant legal provisions under Law Number 28 of 2014 concerning Copyright, supported by doctrinal interpretation and analysis of technological developments in creative production. Results: The findings indicate that AI cannot be recognized as a legal subject or copyright holder under current Indonesian law. Copyright and economic rights are granted exclusively to humans who contribute significant creative input. Furthermore, if AI-generated voices imitate the vocals of deceased singers, permission from rights holders or heirs is required, and the use remains subject to royalty regulations. Novelty: This study provides a timely legal perspective on the intersection of AI and intellectual property rights, emphasizing the urgency for adaptive reforms in Indonesian copyright law to address emerging challenges in AI-generated creative works.